Quiet solar geomagnetic variations at observatories in symmetrical latitudes during a minimum of solar activity - Van Zele, María Andrea (1993)
Solar geomagnetic variations on quiet days (Sq), neglecting the small lunar contribution (L), are compared for Teoloyucan (geogr.lal 19°45', long. -99° 11') and La Quiaca (geogr.lat -22°06', long.-65°36’), located in the longitudinal sector of maximum difference between geographic and geomagnetic latitudes, the latter being 29,6° and -10,6°respectively. Given the manifest asymmetry, even during the equinoxes comparable data from Pilar (geogr.lat-31°40', long.-63°53'; geomagn.lat-20,40) are supplied. Noon values of the geomagnetic north component of Sq can be represented by a plane model including an electrojet centered al the dip equator and two ionospheric current systems of greater latitudinal extent Application of this model to the particular group of E-months (March/April-September/October) shows that the distance between the vortices of these current systems and the equator is greater in the northern hemisphere than in the southern. Merely geomagnetic causes cannot account for this discrepancy.